The CAM (Creative–Analytical–Managed) Learning Model in Workplace Transformation and Corporate Training - Ochoa Siguencia, Luis (International Journal of Advanced Corporate Learning (iJAC), 2025)
The Creative–Analytical–Managed (CAM) Learning Model, a unique pedagogical framework, is designed to meet the intricate learning needs of modern corporate environments. Traditional training methods fall short in digital transformation, globalization, and evolving labor markets. CAM, an evidence-based and holistic choice, integrates three interconnected components: Creative, Analytical, and Managed. The Creative component is dedicated to divergent thinking and innovative problem-solving; the Analytical component is committed to critical thinking and data analysis; and the Managed part is concerned with goal-setting, self-management, and project planning. These dimensions work harmoniously to support a dynamic learning process that aligns with adult learning theory and strategic human resource development. This research confirms the CAM model using a mixed-method study with 200 working adult learners from various corporate environments. Quantitative metrics such as confirmatory factor analysis and regression models show that the three dimensions significantly predict training outcomes, with the managed dimension having the greatest unique contribution. Erasmus+ students’ quantitative feedback also validates the viability of the model, attributing increased participation, creative confidence, critical thinking, and project delivery. The CAM model’s flexibility can be realized in various training settings such as digital upskilling, entrepreneurship, leadership, and off-site onboarding. It complements AI-enhanced learning by emphasizing uniquely human capabilities—creativity, judgment, and strategic autonomy—that resist automation. Practically, CAM offers a scalable solution for Human Resources professionals and learning designers seeking to build future-ready, self-directed learners. Theoretically, it bridges critical pedagogy, adult learning, and projectbased education. In spite of the difficulties of implementation, the empirical robustness and diversity of CAM support its continuance as a means of meeting the demands of learning in a progressively sophisticated work setting, solidifying trust in its effectiveness.